Implementation of Honesty Character Education: a Comparative Study of Indonesian and New Zealand Primary Schools - Ulya, Ghonni Afifatul; Hidayat, Muhammad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This research aims to analyse the implementation of honesty character education in elementary schools with a comparative study between Indonesia and New Zealand. Methodology: Employing a qualitative approach, this study relies on a literature review method. Secondary data sources, including articles from online scientific journals, were gathered to explore honesty character education initiatives in both countries. Data analysis techniques encompassed data collection, reduction, presentation, and conclusion. The validity of the findings was ensured through techniques such as check and hack, author validity, and source triangulation. Results: The findings indicate similarities and differences in honesty character education implementation. Indonesia and New Zealand prioritise instilling honesty and integrity in students to foster genuine character development. However, while Indonesia integrates character education into the national curriculum, New Zealand focuses on cultivating an ethically grounded educational environment. Applications/Originality/Value: This research contributes to understanding the implementation of honesty character education in diverse cultural contexts through a comparative study of Indonesia and New Zealand.